Bernard Lonergan’s Method in Theology: A Theologian Questions His Own Understanding - Sala, Giovanni B. (Philosophy & theology, 1997)
Fr. Sala attempts in this article to provide readers and students of Lonergan with a clear, precise, and condensed presentation of his conception of method in theology in today’s context. He does this by sketching the most important stages in the evolution of Lonergan’s thought. The core of this presentation is the analysis of the “human subject in its subjectivity.” Lonergan deals primarily not with the content of theological science but with the operations theologians perform in constructing theology. He endeavors to clarify this subjectivity in all its dimensions. Having given us an analysis of Lonergan’s Verbum articles, Sala goes on to present Lonergan’s Insight under three headings: knowledge, objectivity, and reality. This done, he proceeds to summarize Method in Theology under these headings: the religious dimension of the subject, the structure of theological method, the specific theological principle of a method in theology, and the authentic subject as the foundation for theological reflection. The article is a masterly presentation of a vast area of research and a good introduction to Lonergan’s works. This article appeared in Theologie und Philosophie 63 (1988) 34-59 and was titled: “B. Lonergans Methode der Theologie: Ein Theologe hinterfugt seinen eigenen Verstand.” Von Giovanni B. Sala, S.J.